2001
DOI: 10.1023/a:1012211828319
|View full text |Cite
|
Sign up to set email alerts
|

Desferri-exochelin induces death by apoptosis in human breast cancer cells but does not kill normal breast cells

Abstract: A major goal of cancer chemotherapy is the identification of cytotoxic compounds that are highly selective for cancer cells. We describe here one such compound - a novel iron chelator, desferri-exochelin 772SM. This desferri-exochelin has unique chemical and pharmacological properties, including extremely high iron binding affinity, the capacity to block iron-mediated redox reactions, and lipid solubility which enables it to enter cells rapidly. At low concentrations, this desferri-exochelin kills T47D-YB and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 33 publications
0
25
0
Order By: Relevance
“…Both these anti-TfR mAbs and other anti-TfR mAbs have been shown previously to have synergistic antiproliferative effects on human cell lines cells in vitro and inhibit the growth and induce tumor regressions of established s.c. tumors of CCRF-CEM leukemia cells in nude mice (17,34). Breast cancer cell lines have also been shown to express high levels of TfR compared with normal breast epithelial cells and are more sensitive to iron depletion, which leads to inhibition of cell proliferation (35)(36)(37). The synergistic inhibition of proliferation induced by two anti-TfR mAbs is likely related to the ability of the mAbs to bind to different epitopes in TfR, resulting in receptor cross-linking, and block in iron uptake, which is required for DNA synthesis (9,38).…”
Section: Discussionmentioning
confidence: 99%
“…Both these anti-TfR mAbs and other anti-TfR mAbs have been shown previously to have synergistic antiproliferative effects on human cell lines cells in vitro and inhibit the growth and induce tumor regressions of established s.c. tumors of CCRF-CEM leukemia cells in nude mice (17,34). Breast cancer cell lines have also been shown to express high levels of TfR compared with normal breast epithelial cells and are more sensitive to iron depletion, which leads to inhibition of cell proliferation (35)(36)(37). The synergistic inhibition of proliferation induced by two anti-TfR mAbs is likely related to the ability of the mAbs to bind to different epitopes in TfR, resulting in receptor cross-linking, and block in iron uptake, which is required for DNA synthesis (9,38).…”
Section: Discussionmentioning
confidence: 99%
“…No cytotoxicity was evident when normal human mammary epithelial cells were treated at 5 or 20 M, although a growth arrest was seen (Pahl et al, 2001). These effects were prevented when either cell line was incubated with the iron-loaded D-Exo, indicating that the iron-binding ability of this ligand was responsible for its antiproliferative activity (Pahl et al, 2001). Further studies examining D-Exo 772SM on DNA synthesis demonstrated a 95% to 97% reduction of [ 3 H]thymidine incorporation in both the normal and cancerous breast cell lines after a 6-h incubation (Pahl et al, 2001).…”
Section: Evolution Of Iron Chelatorsmentioning
confidence: 95%
“…4) as an antiproliferative agent. An in vitro study examining the effect of 20 M D-Exo 772SM on MCF-7 breast cancer cells illustrated potent antineoplastic activity where all cells were killed after 4 days of treatment (Pahl et al, 2001). No cytotoxicity was evident when normal human mammary epithelial cells were treated at 5 or 20 M, although a growth arrest was seen (Pahl et al, 2001).…”
Section: Evolution Of Iron Chelatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Furthermore, the ligand was also shown to cause tumor cell death via inducing apoptosis. 15 It is also interesting to note that there are studies that suggest Fe is required for angiogenesis. Indeed, Carlevaro et al 16 demonstrated that the Fe-transport molecule, transferrin, is a major angiogenic stimulus released by hypertrophic cartilage.…”
Section: Dear Sirmentioning
confidence: 99%